Social innovation in a developing country: invention and diffusion of the Brazilian cooperative incubator - Almeida, Mariza; Mello, Jose Manoel Carvalho De; Etzkowitz, Henry (International Journal of Technology and Globalisation, 2012)
The incubator model of a support structure to develop high-tech ﬁrms from academic research was imported from the USA to Brazil, where it serves a variety of economic and social purposes. The Brazilian cooperative incubator is a creative reinterpretation of the business incubator model to advance social innovation. It addresses issues of social exclusion, poverty and unemployment by empowering favela residents to create their own jobs. Having diffused broadly, the Brazilian cooperative incubator allows us to address the issue of growth in social enterprises. This paper employs a triple helix dynamic model, including government (local, regional and national), academic (different types of universities, industry (ﬁrms of varying scale and sector, industry associations) and NGOs (non governamental organizations) to explain the diffusion and expansion of this innovation in social entrepreneurship.
Number: 3 N'AVONS PAS ACCÈS VERSION ORIGINALE. http://www.inderscience.com/link.php?id=48326; Version disponible sur Academia.edu
Keywords: Amérique latine; Version libre-accès Academia.edu